A Capital Market Union for Europe - Bhatia, Ashok (Staff Discussion Notes; Staff Discussion Notes, 2019)
This note weighs the merits of a capital market union (CMU) for Europe, identifies major obstacles in its path, and recommends a set of carefully targeted policy actions. European capital markets are relatively small, resulting in strong bank-dependence, and are split sharply along national lines. Results include an uneven playing field in terms of corporate funding costs, the rationing out of collateral-constrained firms, and limited shock absorption. The benefits of integration center on expanding financial choice, ultimately to support capital formation and resilience. Capital market development and integration would support a healthy diversity in European finance. Proceeding methodically, the note identifies three key barriers to greater capital market integration in Europe: transparency, regulatory quality, and insolvency practices. Based on these findings, the note urges three policy priorities, focused on the three barriers. There is no roadblock-such steps should prove feasible without a new grand bargain.